Prevalence of noise-induced hearing loss among woodworkers in Nepal: a pilot study. (January 2015) - Robinson, Tim; Whittaker, Joshua; Acharya, Aanand; Singh, Devesh; Smith, Michael
<x content-type="archive" xml:space="preserve">Abstract</x> Background: The woodworking industry represents an important cause of occupational noise-induced hearing loss (NIHL), a significant yet underappreciated problem in many developing countries. Objectives: To describe the prevalence of occupational NIHL among woodworkers in Nepal and measure noise levels at workplaces. Methods: We conducted a cross-sectional study with 124 woodworkers (88 carpenters, 36 sawyers), recruited through convenience sampling from 26 workplaces. Pure-tone audiometry between the frequencies 0·5 and 8 kHz ascertained participants' hearing status, and noise readings were taken at selected workplaces. Results: In all, 31% of carpenters and 44% of sawyers met criteria for NIHL, with 7 and 17% meeting World Health Organization (WHO) criteria for hearing impairment (HI), respectively. Noise levels at various workplaces ranged from 71·2 to 93·9 dBA. Conclusions: Woodworkers in Nepal are at risk of occupational NIHL. As the industry develops, this problem will likely become more extensive, highlighting the need for workplace interventions and additional research.